PENGARUH PDRB SEKTOR INDUSTRI, TRANSPORTASI, DAN PERTANIAN TERHADAP EMISI CO2 DI PROVINSI JAWA TENGAH - Hela, Syafina; Ekawaty, Marlina (Journal of Development Economic and Social Studies, 2024)
This study aims to determine the effect of GRDP in the industrial, transportation, and agricultural sectors on carbon dioxide (CO2) emissions in Central Java Province. This study is important because there has been a change in the structure of the economy from agriculture to industry and services in Central Java, which has sparked fears of an increase in CO2 emissions that damage the quality of the environment. The objectives of this study were achieved by using time series data from 2001-2020 and analyzed by multiple linear regression. The results of this study indicate that the GRDP of the industrial sector has a positive and significant effect on CO2 emissions, the GRDP of the transportation sector has a negative and significant effect, while the GRDP of the agricultural sector has no effect.